Computational methods for the assessment of empathic synchrony - Bizzego, Andrea (Springer Nature, 2021)
The synchronization of physiological signals between persons is a well-known proxy of empathy. However, it is also influenced by physiological and environmental factors that should be discriminated to correctly characterize the empathy component. We discuss a framework to compute synchrony and introduce physynch, an open-source package developed to easily replicate its computational procedures. We adopted physynch to study the synchrony of the electrodermal activity in 61 male-female dyads with different types of relationship: strangers (18 dyads), friends (23 dyads) and lovers (20 dyads). The findings confirm previous results on Heart Rate Variability synchrony and suggest that synchrony is influenced by the type of relationship and is stronger in dyads of strangers. physynch is made available for download and use for researchers interested in measuring physiological synchrony.